Youth Restiveness and Leadership Problem in Nigeria - Oke, Solomon J. Oke; Ahoton, Samuel A. Ahoton (African Journal of Stability and Development (AJSD), 2024)
Youth restiveness has escalated in contemporary Nigeria, becoming a source of national concern. Unfortunately, Nigeria cannot thrive and make any meaningful progress if it continues to being plagued by youth restiveness. Being the most populous country in Africa and one of the most populous nations globally, Nigeria has a higher population of young people, that are restive than most countries of the world. Nigeria’s peace, security, progress and unity as a nation are under siege due to this phenomenon. However, the causes of youth’s restiveness are linked to unemployment, lack of basic and quality education, inadequate provision of welfare package, lack of infrastructural facilities, inequality and lack of other basic social amenities. The increased and negative effects of youth restiveness are present everywhere in Nigeria today as kidnapping, ritual killings, militancy, crimes, violence, bombing, destruction of government properties, cultism, armed robbery and political instability, among a host of others, bedevil the country. However, in some ways, youth restiveness could be linked to the failure and bad leadership style in Nigeria. The conflict theory will be used to explain threatening situations like war, killings, revolution, domestic violence, cybercrime and others. It is however pathetic that successive governments in Nigeria have failed to provide solutions to this menace through the provision of basic and quality education to teaming Nigeria youths, as well as employment opportunities, and other effective empowerment programmes. This study argues that for us to curtail and control youth restiveness in Nigeria, the government should harness youth skills and talents, ensure the provision of employment opportunities, and put in place quality education. The strength, wisdom and leadership skills of the youths should be channelled to various leadership positions in the society for growth.